2009
DOI: 10.1099/vir.0.012021-0
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in lymphoid tissues of calves inoculated with non-cytopathic bovine viral diarrhea virus genotype 1: activation of effector caspase-3 and role of macrophages

Abstract: The mechanisms responsible for lymphocyte apoptosis in bovine viral diarrhoea have not yet been clarified. Previous work suggests that bovine viral diarrhea virus (BVDV) is only directly responsible for the destruction of a small number of lymphocytes. The aim of this study was to clarify, in vivo, the role of macrophages in lymphocyte destruction through indirect mechanisms linked to the biosynthetic activation of these immunocompetent cells on ileal Peyer's patches, as well as the distribution and quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
(58 reference statements)
6
20
1
Order By: Relevance
“…Traditional methods of virus isolation quantify the amount of virus recovered from a fixed volume of blood irrespective of the cell numbers in the sample (Young et al., 2006), which during acute BVDV infection will fluctuate because of leucopoenia (Ridpath et al., 2007; Pedrera et al., 2009a; b). Thus, to quantify RNA using RT‐qPCR, controls have to be used to standardize the amounts of RNA obtained from samples from different animals taken on different days (Leutenegger et al., 2000; Young et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional methods of virus isolation quantify the amount of virus recovered from a fixed volume of blood irrespective of the cell numbers in the sample (Young et al., 2006), which during acute BVDV infection will fluctuate because of leucopoenia (Ridpath et al., 2007; Pedrera et al., 2009a; b). Thus, to quantify RNA using RT‐qPCR, controls have to be used to standardize the amounts of RNA obtained from samples from different animals taken on different days (Leutenegger et al., 2000; Young et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate the important role of lymphoid tissues in virus replication as well as the role of immunocompetent cells in the spread of BVDV throughout the body. In this sense, monocytes–macrophages and dendritic cells have been showed as the main target cells involved (Liebler‐Tenorio et al., 2003a,b, 2004; Pedrera et al., 2009a,b). The large increase in virus in the tonsils on day 9 p.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 On the other hand, the increase in B-lymphocyte numbers was more marked and occurred earlier in infection in those calves inoculated with BHV-1 alone. The attenuated Blymphocyte response observed in the BVDV/BHV-1 group may be linked to a severe lymphocyte depletion in BVDV target lymphoid organs, a lesion that has already been described in calves 46 and in other in vivo infections with BVDV, 31,32,37,38,43 in which the depletion has been correlated to the action of apoptotic mechanisms developed during BVD. A difference between groups was observed in the behavior of CD8þ, CD4þ, and Foxp3þ regulatory T cells, as well as in the different cytokines studied in response to the secondary infectious agent.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion was due to massive lymphocyte apoptosis with concurrent activation of caspase-3 as analyzed by immunohistochemistry. 30 However, lymphocyte apoptosis in the gut-associated lymphoid tissue (GALT) was paralleled by an increase in caspase-8 and rather a decrease in caspase-9, indicating that the extrinsic rather than the intrinsic pathway of apoptosis might predominate in acute BVDV infections. 29 This is in contrast to the results presented in this study that showed that the intrinsic pathway is a key element in the induction of apoptosis in MD pathogenesis in persistently infected calves.…”
Section: Discussionmentioning
confidence: 99%